A simple and convenient route to synthesize novel hyperbranched Poly(amine ester) with multicolored fluorescence. (17th December 2019) - Du, Yuqun; Bai, Tian; Yan, Hongxia; Zhao, Yan; Feng, Weixu; Li, Wanqing
Abstract: Multicolored fluorescence stemed from the nonconventional luminescent polymers without aromatic units is an interesting and meaningful property. So far, a few such polymers bearing multicolored fluorescence are reported; its species, however, are relatively little. Herein, we synthesized a kind of novel water-soluble hyperbranched poly(amine ester) (HPAE) via a straightforward transesterification polycondensation reaction using inexpensive and easily available chemicals. Intriguingly, the pure HPAE could emit blue, green and red luminescence when irradiated by different excitation wavelengths. The TEM result shows that the synergy effect of intra-/intermolecular hydrogen bonds and hydrophobic effect could induce the HPAE to self-assemble and form supramolecular HPAE in water. Such supramolecular HPAE further promote to form stronger through-space conjugation, thus which is favourable for the emission. In addition, the significant solvent and pH dependence profiles of luminescence intensity are also observed. In particular, the HPAE can be used to detect metal ions, and there is strong selective quenching in respect of Fe 3+ . Therefore, the HPAE show a potential probe for Fe 3+ . Graphical abstract: Image 1 Highlights: Synthesis of a novel hyperbranched poly(amine ester) (HPAE). The pure HPAE could emit multicolored fluorescence including blue, green and red under different excitation wavelengths. The synergy effect of intra-/intermolecular hydrogen bonds and hydrophilicity could lead to form the supramolecular HPAE. HPAE as a potential luminescence probe for detecting Fe 3+ .